2022
DOI: 10.1177/23779608221084977
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mutual Support on Burnout among Intensive Care Unit Healthcare Professionals

Abstract: Introduction Burnout among healthcare professionals in intensive care units (ICUs) is a serious issue that leads to early retirement and medication errors. Their gender, lower years of experience, and lower education have been reported as risk factors. Simultaneously, mutual support—commonly referred to as “back-up behavior,” in which staff members support each other—is critical for team performance. However, little is known about the influence of mutual support among ICU healthcare professionals on burnout. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 50 publications
0
7
0
4
Order By: Relevance
“…The authors [ 20 ] reported that nurses’ emotional exhaustion level in the ICU during the COVID-19 pandemic was moderate, with 34.1% having a high level of emotional exhaustion, 2.3% a medium level and 13.5% a low level. Nurses who had worked in the ICU for a long time had higher dynamic exhaustion values than those allocated to the ICU during the COVID-19 pandemic [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors [ 20 ] reported that nurses’ emotional exhaustion level in the ICU during the COVID-19 pandemic was moderate, with 34.1% having a high level of emotional exhaustion, 2.3% a medium level and 13.5% a low level. Nurses who had worked in the ICU for a long time had higher dynamic exhaustion values than those allocated to the ICU during the COVID-19 pandemic [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the authors [ 20 ], 11.4% of the nurses who worked during the COVID-19 pandemic in the ICU had a high level of depersonalisation, 68.2% a medium level and 20.4% a low level. In general, higher levels of depersonalisation were observed in men with professional experience between 11 and 20 years, compared to women with the same amount of professional experience [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nota: **Demuestra que la correlación es significativa a un nivel de 0.01 bilateral Es importante mencionar que, en investigaciones anteriores (Haruna et al, 2022), se ha observado una correlación entre la variable apoyo mutuo y el trabajo en equipo virtual. Sin embargo, los resultados de esta investigación no presentaron dicha correlación, esto se debe a dos razones.…”
Section: Resultados Del Modelo De Investigaciónunclassified
“…Además, al carecer de cultura de apoyo mutuo, representa un problema individual u organizacional, ya que se ha comprobado que un menor apoyo mutuo se asocia con un mayor agotamiento. Cuando no se practica este concepto en un equipo de trabajo disminuye su oportunidad de poder crecer y desarrollar completamente su talento, esta acción no va a permitir que el equipo siga adelante por lo que no va a poder cumplir con su meta, representando un agotamiento y falta de motivación generando incertidumbre (Haruna et al, 2022).…”
Section: Apoyo Mutuo (X3)unclassified
See 1 more Smart Citation